1976
DOI: 10.1111/j.1365-2133.1976.tb04386.x
|View full text |Cite
|
Sign up to set email alerts
|

The succinic dehydrogenase and cytochrome c oxidase activities of guinea-pig skin after mild heat damage

Abstract: Succinic dehydrogenase and cytochrome c oxidase activities of guinea-pig ear skin were found to be less sensitive than oxygen uptake to mild heat damage. It therefore appears that the failure of oxygen uptake following thermal injury is not directly due to inactivation of the enzymes of the respiratory chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The data presented in this paper demonstrate that the respiration of heat-damaged skin can be protected if a substrate is supplied which is directly oxidizable by the respiratory chain. These findings also narrow the area in which the origin of heat-produced failure of oxygen uptake must be sought, since it has previously been shown that glycolysis is also more resistant to heat inhibition than is oxygen uptake (Carney et al, 1976a). The earliest heat-induced metabolic failure must therefore occur within the Krebs cycle (Fig.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The data presented in this paper demonstrate that the respiration of heat-damaged skin can be protected if a substrate is supplied which is directly oxidizable by the respiratory chain. These findings also narrow the area in which the origin of heat-produced failure of oxygen uptake must be sought, since it has previously been shown that glycolysis is also more resistant to heat inhibition than is oxygen uptake (Carney et al, 1976a). The earliest heat-induced metabolic failure must therefore occur within the Krebs cycle (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…In skin the enzymes of the respiratory chain are relatively resistant to heat damage. Previous work by Carney et al (1976b) demonstrated that pre-treatment temperatures of 45 3 C and 45 9 C were required to produce 50",, inhibition of succinic dehydrogenase and cytochrome C oxidase activities respectively. The data presented in this paper demonstrate that the respiration of heat-damaged skin can be protected if a substrate is supplied which is directly oxidizable by the respiratory chain.…”
Section: Discussionmentioning
confidence: 99%